School readiness for Computer Based National Examination implementation in East Aceh, Aceh Province - Indonesia - Iffah, Dara (Kulliyyah of Education, International Islamic University Malaysia, 2017)
The purpose of this study is to find out to what extent schools are ready for accepting Computer Based National Examination (CBNE) in terms of infrastructure, human resource, government support and administrative role. This study employed a qualitative case study approach consisting of three schools from three distinct categories such as general secondary school, secondary boarding school and vocational school in East Aceh District. All the selective schools have implemented the CBNE system for students. For collecting data, the researcher conducted interviews with the selected schools' principals. The research findings report on the variety of preparation that these three schools had taken in implementing CBNE. In terms of infrastructure and human resource readiness, they followed the instruction provided by the Ministry of Education, Indonesia, while there is also additional equipment that they prepared as well to maintain the electric supply. Moreover, schools got both financial and non-financial supports from the government to launch the CBNE in their schools. In terms of administration role, the schools conducted training for students and teachers tomanage the session and community involvement in conducting CBNE.